The Infant Version of the Laboratory Temperament Assessment Battery (Lab-TAB): Measurement Properties and Implications for Concepts of Temperament - Planalp, Elizabeth M.; Van Hulle, Carol; Gagne, Jeffrey R.; Goldsmith, H. Hill (Frontiers in Psychology, 2017)
We describe large-sample research using the Infant Laboratory Temperament Assessment Battery (Lab-TAB; Goldsmith & Rothbart, 1996) in 1076 infants at 6 and 12 months of age. The Lab-TAB was designed to assess temperament dimensions through a series of episodes that mimic everyday situations. Our goal is to provide guidelines for scoring Lab-TAB episodes to derive temperament composites. We also present a set of analyses examining mean differences and stability of temperament in early infancy, gender differences in infant temperament, as well as a validation of Lab-TAB episodes and composites with parent reported Infant Behavior Questionnaire (IBQ; Rothbart, 1981) scales. In general, laboratory observed temperament was only modestly related to parent reported temperament. However, temperament measures were significantly stable across time and several gender differences that align with previous research emerged. In sum, the Lab-TAB usefully assesses individual differences in infant emotionality.